Basilar and Bilateral Carotid Dolichoectasia with Spontaneous Dissection of C2 Segment of the Internal Carotid Artery - Borota, L.; Jonasson, P. (American Journal of Neuroradiology, 2006)
Summary: We describe a previously unreported case of cranial arterial dolichoectasia associated with spontaneous dissection of the petrous (C2) segment of the internal carotid artery (ICA) with 2 patent lumena. Dolichoectasia of the cranial arteries and different types of double lumen of ICA are discussed. A review of previously reported cases is included.